Magnetic particle spectroscopy-based bioassays: methods, applications, advances, and future opportunities. (18th February 2019) - Wu, Kai; Su, Diqing; Saha, Renata; Wong, Dillon; Wang, Jian-Ping
Abstract: Since the first system was established and reported in 2005, magnetic particle imaging (MPI) has emerged as a non-invasive tomographic technique that has proven useful in diagnostic imaging. Magnetic particle spectroscopy (MPS), alternatively called magnetization response spectroscopy, is a novel measurement method that closely relates to MPI. An MPS system can be interpreted as a 0D MPI scanner consisting of excitation field coils and pickup coils. In MPS, a sinusoidal magnetic field with sufficiently large amplitude is applied to superparamagnetic iron oxide nanoparticles (SPIONs), which periodically drives their magnetization into and out of saturation. Their magnetic responses, which contain unique harmonics, are recorded and separated into their spectral components. While prototypes of MPI systems are still in their testing stages, MPS has been actively explored as a portable, highly-sensitive, cheap, in vitro, and easy-to-use bioassay testing kit. In this review, we briefly discuss the superparamagnetism and magnetic relaxation mechanisms associated with MPS measurements. We summarize the recent progress in the various MPS detection modes and, also, MPS-based bioassays. Finally, this review concludes with an insight of the state of art and future trends of MPS-based bioassays.